Designing the framework to implement the sustainability accounting concept in the small business organization: a conceptual approach / Putu Sukma Kurniawan - Kurniawan, Putu Sukma (2019)
This research aims to design the initial framework to help the small business organization implement the sustainability accounting concept. The basic principle in this research is the small business organization is the part of our big economic system and the small business organization has a big responsibility to implement the sustainability accounting concept in their business activities. Based on previous research and works of literature, the implementation process of sustainability concept (and also sustainability accounting) can improve the company's internal business and build a strong connection with the company's stakeholders. Therefore, the implementation process of sustainability accounting concept is important for the small business organization.